Lactobacillus plantarum AJ2 isolated from naturally fermented sausage and its effects on the technological properties of Milano-type salami Lactobacillus plantarum AJ2 isolado de salame naturalmente fermentado e seus efeitos nas propriedades tecnológicas do salame tipo Milano - Maristela Cortez Sawitzki (Food Science and Technology, 2008)
L. plantarum, strain AJ2, was isolated from naturally fermented sausage manufactured in the Southern region of Brazil and inoculated in Milano-type salami. The lactic culture exhibited the ability of growing in the product, decreasing pH in the first seven days of fermentation/maturation and the residual levels of nitrite and nitrate, as well as peroxide and TBARS values. The inoculated sausage had the highest intensity for brightness and red color, but did not present a difference in chemical composition and fatty acid composition, compared to the control. L. plantarum, cepa AJ2, foi isolado de salame naturalmente fermentado, fabricado na região Sul do Brasil e inoculado em salame tipo Milano. A cultura láctica apresentou habilidade para crescer no produto, promover a redução do pH nos primeiros sete dias de fermentação/maturação e dos níveis residuais de nitrito e nitrato, assim como menores valores de peróxidos e TBARS. O salame inoculado teve maior intensidade de brilho e da cor vermelha, mas não apresentou diferenças significativas na composição química e na composição de ácidos graxos, em relação ao controle.